Dampak Investasi Pariwisata terhadap Fungsi Permukiman di Ubud Bali: Transformasi Keruangan, Sosial dan Ekonomi - Gaek Raka Juniawati (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
The entry of tourism to Bali because it has a stunning natural beauty is no exception Ubud. Tourism provides many changes. Based on local sources, as well as the results of in-depth interviews with Ubud community leaders, the initial entry of tourism was because Ubud has an interesting culture. In addition, the initial capital attracts tourists to come to Ubud through its social values, invites tourists to participate in social activities, provides opportunities for tourists to become part of Ubud itself. This causes the development of tourism to increase, and encourages people to rent out their houses which we usually call homestays. Seeing this opportunity, investors began to offer funds to develop residential areas for local communities. However, the increase in tourism, of course, will affect the arrangement of settlements in Ubud. In view of this, the research aims to analyze the transformations that arise and provide an overview of changes in settlements in Ubud. The phenomena found in the field that investment has an impact on space, economy and social. This study uses a qualitative method with a phenomenological approach with data collection by field observations, in-depth interviews, and field analysis. The results of the study, which are in the form of macro and micro mapping images of the changes that occur, are expected to be able to provide a picture of changes in the functioning that occur in the Ubud Area in a spatial, socio-cultural, and economic manner properly.